2013
DOI: 10.1681/asn.2012070646
|View full text |Cite
|
Sign up to set email alerts
|

Extending Prednisolone Treatment Does Not Reduce Relapses in Childhood Nephrotic Syndrome

Abstract: Prolonged prednisolone treatment for the initial episode of childhood nephrotic syndrome may reduce relapse rate, but whether this results from the increased duration of treatment or a higher cumulative dose remains unclear. We conducted a randomized, double-blind, placebo-controlled trial in 69 hospitals in The Netherlands. We randomly assigned 150 children (9 months to 17 years) presenting with nephrotic syndrome to either 3 months of prednisolone followed by 3 months of placebo (n=74) or 6 months of prednis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 31 publications
7
100
0
1
Order By: Relevance
“…Prednisone is the cornerstone of therapy for idiopathic nephrotic syndrome, inducing remission within 4-6 weeks in approximately 90% of cases (7). However, the risk of relapse can be as high as 85% at 5 years, requiring reiteration of prednisone courses, often with the additional use of calcineurin inhibitors.…”
Section: Idiopathic Nephrotic Syndromementioning
confidence: 99%
“…Prednisone is the cornerstone of therapy for idiopathic nephrotic syndrome, inducing remission within 4-6 weeks in approximately 90% of cases (7). However, the risk of relapse can be as high as 85% at 5 years, requiring reiteration of prednisone courses, often with the additional use of calcineurin inhibitors.…”
Section: Idiopathic Nephrotic Syndromementioning
confidence: 99%
“…Only three studies showed adequate allocation concealment [12][13][14], and no studies were blinded. In contrast, three [5][6][7] of the four studies added to the 2015 update demonstrated adequate allocation concealment, and two studies were blinded [5,7].…”
Section: Investigation Of Heterogeneity In Meta-analysesmentioning
confidence: 99%
“…Three large well-designed RCTs were published in 2013-2015 [5][6][7] which evaluated different durations of prednisolone therapy in children with their first episode of SSNS. In their RCT, Teeninga and co-workers [5] randomized 150 children to 3 months of prednisolone therapy and 3 months of placebo, or to 6 months of prednisolone therapy, with both groups receiving approximately the same total dose of prednisolone.…”
Section: Update Of the Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, frequent relapses and steroid dependence are disease outcomes in about 20%-60% of affected children. 4 Conversely, FSGS is characterized by steroid resistance in a majority of patients, steroid sensitivity in only about 20% of cases, as well as a high risk of developing end-stage renal disease. 5 Various hypotheses regarding the pathogenesis of the syndrome have evolved over time, with the current paradigm revolving around a podocytopathy.…”
mentioning
confidence: 99%